2018
DOI: 10.1111/nph.15106
|View full text |Cite
|
Sign up to set email alerts
|

Plant stem cells and de novo organogenesis

Abstract: Contents Summary 1334 I. Introduction 1334 II. Regeneration-initial cell: the origin of regeneration 1335 III. Acquiring regeneration competency: the essential intermediate step for hormone-induced regeneration 1335 IV. Hormonal induction of stem cell regulators: the program for de novo establishment of apical meristems 1337 V. Conclusions and perspectives 1337 Acknowledgements 1338 Author contributions 1338 References 1338 SUMMARY: High cellular plasticity confers remarkable regeneration capacity to plants. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 38 publications
1
58
0
Order By: Relevance
“…Previous studies had shown that callus could be induced from aerial organs and resembles the tip of a root meristem (Sugimoto et al, 2019). The root meristem regulator genes, such as WOX5 and WOX11, had been verified to play important roles in callus initiation in A. thaliana and Oryza sativa (Hu et al, 2017;Cheng et al, 2018;Liu et al, 2018a;Sang et al, 2018). In this study, ZmWOX11 showed peak expression at D2 and dropped afterward.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies had shown that callus could be induced from aerial organs and resembles the tip of a root meristem (Sugimoto et al, 2019). The root meristem regulator genes, such as WOX5 and WOX11, had been verified to play important roles in callus initiation in A. thaliana and Oryza sativa (Hu et al, 2017;Cheng et al, 2018;Liu et al, 2018a;Sang et al, 2018). In this study, ZmWOX11 showed peak expression at D2 and dropped afterward.…”
Section: Discussionsupporting
confidence: 49%
“…Whole plants can be regenerated from tissue samples such as branch cuttings or detached leaves via a callus [1], a mass of undifferentiated cells able to initiate shoot- and root-stem cells in the presence of the appropriate phytohormones [2]. Several genes have been shown to function in regenerating cells [3, 4]; however, the elucidation of the transcriptome profiles involved in the regeneration process of each cell is a major challenge as it is not currently possible to separate and identify the limited numbers of stem cells that randomly emerge in a callus during regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…It is a phenyl-urea compound that has been substantiated to have the cytokinin potency across plant species [24][25][26][27]. Growth regulators' signal conversions into metabolic activities and developmental morphologies in cells or organisms have been established in biology [28][29][30][31][32][33]. The concept is broadly utilized for downstream applications particularly in cell, tissue, and organ cultures as well as plant transformation across plant species [24,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%